Femininity in Flight : A History of Flight Attendants - Barry, Kathleen M. (Kathleen Morgan) (Book collections on Project MUSE., 2007)
Considers flight attendants as cultural icons, looking at the history of the occupation and how attendants redeployed the "glamorization" used to sell air travel to campaign for professional respect, higher wages, and women's rights.